Profiling the coaches of Norway. A national survey report of sports coaches & coaching - Chroni, S.; Medgard, M.; Nilsen, D. A.; Sigurjónsson, T.; Solbakken, T. (Skriftserien, 2018)
In 2017, Inland Norway University of Applied Sciences surveyed a large number sports coaches across Norway. The survey sought to get to know the men and women who coach the children, youth, and adults of Norway. The data of this survey project, titled Profiling the Coaches of Norway (PROCON), is based on responses from 5977 coaches, 4404 men and 1559 women aged from 15 to 83 years old. The coaches represented 104 sports from 49 federations, and came from every county in Norway. The present publication reports on what we learned about the coaches and coaching in Norway; the educational and sports backgrounds they come from, the experience they bring with them, the sports knowledge and skills they possess; how they think about learning and their future in coaching; what hinders their learning and advancement as coaches, and why some of them stopped coaching. While the PROCON sample is one of the largest captured in a coaches` survey study worldwide, we cannot be sure how representative it is of Norway`s sports coaches, as the total number of coaches working within sports across all levels nationwide is unknown.